Documenti sugli ebrei a Grottaglie nei secoli XV-XVI - Quaranta, Rosario (Sefer yuḥasin ספר יוחסין | Review for the History of the Jews in South Italy | Rivista per la storia degli ebrei nell’Italia meridionale, 2013)
In questo articolo si presenta il primo tentativo di tracciare una storia degli ebrei a Grottaglie. Particolare attenzione è data a un piccolo ma significativo gruppo di nuovi documenti: 1) un registro della Chiesa Madre dell’Annunziata, le cui prime annotazioni risalgono al 1417; 2) una pergamena del 1486 conservata presso l’Archivio Capitolare di Grottaglie; 3-4) due atti notarili del 1531-32, stipulati presso il notaio Federico Cirasino; 5) gli atti della visita pastorale compiuta a Grottaglie nel 1577 dall’arcivescovo di Taranto Lelio Brancaccio. Documents on the Jews of Grottaglie in the 15th and 16th Centuries According to some documents and a constant tradition, there existed in Grottaglie an active Jewish community between the late Middle Ages and the Early 16th century. According to local scholars, the Jews settled in the ravine called Fullonese in order to devote themselves to the dyeing and tanning of leather, as the toponym suggests. Allegedly the Jews disseminated the culture of pomegranate in Grottaglie, the fruit being possibly used in the dyeing process. Later on, the Jews settled in a neighborhood called the “Giudeca”, in the south-west part of the town, near Porta S. Antonio Abate. In the same district there was a church called Santo Stefano dei Giudei. The present article is a first attempt to sketch a documentary history of the Jews in Grottaglie. It draws on a small but significant set of documents: 1) a register of the Chiesa Madre dell’Annunziata, whose earliest records date back to 1417; 2) a parchment of 1486 preserved in the Capitular Archive of Grottaglie; 3-4) two notarial acts of 1531-32, prepared by the notary Federico Cirasino; and 5) the record of a pastoral visit in Grottaglie by the Archbishop of Taranto Lelio Brancaccio in 1577.